The implementation of song lyric “I Have a Dream by Westlife” to improve students’ vocabulary of verbs in the seventh grade students of MTsN Sidorejo Madiun - Ratna Dewi Wijayanti (Universitas PGRI Madiun, 2017)
English as an international language has important role in human life. The functions of learning English in Junior High School are; first, by studying English students are expected to have a means to develop their knowledge of science, technology and culture. The second is students are expected to be able to support the development of tourism. Students must be able to use a lot of vocabulary of English, if they want to be successfull in learning. Vocabulary is an important element in language besides pronunciation and grammar. We can’t express ideas in English without learning English vocabulary.Based on the explanation above, the researcher is interested in conducting research titled “ The Implementation Of Song Lyric “I Have A Dream By Westlife” To Improve Students’ Vocabulary Of Verbs In The Seventh Grade Students Of MTsN SIDOREJO Tiron Madiun In The Schooling Year 2014/2015”.Music and song are included in teaching media, the use of music and song in the classroom can stimulate very positive associations to someone who study language. The result of the analyzing data indicates that the uses of song lyric in teaching vocabulary of verbare divided into two steps. The first is preparation steps. The preparations steps includes prepare the material, stabling instructional purpose, prepares the lesson plan and syllabus. The second is learning process. The learning process includes pre-activity, whilst-activity, and post-activity.